Development and characterization of a new natural fiber reinforced thermoplastic (NFRP) with Cortaderia selloana (Pampa grass) short fibers. (16th June 2017) - Jordá-Vilaplana, A.; Carbonell-Verdú, A.; Samper, M.D.; Pop, A.; Garcia-Sanoguera, D.
Abstract: In this work, fully bio-based thermoplastic composites are manufactured with bio-based polyethylene (from sugarcane) and short fibers coming from Cortaderia selloana (CS) wastes. These wastes are characterized by high cellulose content, which can provide high stiffness to the polymeric matrix. The effect of Cortaderia selloana short fibers on thermal properties has been evaluated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The effect of the filler load on mechanical properties has also been evaluated by tensile and impact tests as well as the effects of different coupling agents. Fiber-matrix interactions have been studied by scanning electron microscopy (SEM). The addition of 15–30 wt% Cortaderia selloana short fiber leads to high elastic and flexural modulus without remarkable changes in thermal degradation of the polymer composite. Graphical abstract: